Pengaruh Kebijakan Pemutihan Pajak Kendaraan Bermotor, Kualitas Pelayanan, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Di Provinsi Lampung - Andini Rizqita Putri; Marselina Marselina (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to analyze the effect of the Motor Vehicle Tax Amnesty Policy, Service Quality, and Tax Sanctions on Taxpayer Compliance in Lampung Province in 2023. Taxes function as a source of income used to implement various public services and infrastructure. Taxpayer compliance is a tax payment to encourage development and public welfare. The low level of motor vehicle taxpayer compliance in Lampung Province is indicated by the high number of vehicles that are in arrears in taxes each year. If taxpayers are compliant in paying their taxes, state revenue will increase. However, taxpayer compliance is one of the problems that can trigger obstacles to tax collection. This study uses a quantitative method with a descriptive approach, using primary data obtained through distributing questionnaires. Using multiple linear regression analysis methods to test the relationship between tax amnesty policies, service quality, tax sanctions, and taxpayer compliance. the results of the study show that tax amnesty policies and tax sanctions have a significant effect on taxpayer compliance, while service quality has no effect on taxpayer compliance. Simultaneously, these three variables have a significant effect on taxpayer compliance. These findings indicate the importance of incentive policies and sanction enforcement as an effort to increase regional revenue through tax compliance.